Johannes Chrysostomus und der Neunizänismus: Eine Spurensuche in ausgewählten Predigten des antiochenischen Presbyters - Karmann, Thomas R. (Sacris erudiri, 2012)
John Chrysostom was ordained a presbyter by bishop Flavianus in Antioch in 386, thereby also accepting the office of a preacher at a time when the Arian controversy was at the close. The origins of the Neo-Nicene theology are believed to lie in Chrysostom’s community in the early 360s, i.e. with its former bishop Meletius. This article seeks to analyse to what extent Neo-Nicene theology is mirrored in the homilies which Chrysostom delivered during his time in Antioch. Before dealing with this question in three consecutive steps, a brief overview of Chrysostom’s work De sacerdotio will be given, in which he addresses the connection between preaching and Trinitarian theology in a theoretical manner. After that, John Chrysostom’s catechetical sermons, most notably Homilia catechetica 3/1, will be surveyed in a first step. In doing so, the authenticity of this sermon will be discussed and H.-J. Vogt’s approach examined critically. In a second step, the article will focus on the homilies against the Anomoeans, and the question will be raised to what extent Chrysostom uses Neo-Nicene terminology in response to Neo-Arianism. In a last step, the question will be raised whether Chrysostom’s homilies take issue with the Ultra-Nicene community of Antioch led by Paulinus and Evagrius. This article holds that John Chrysostom, who very clearly associates himself with the Neo-Nicene community of Antioch in an ecclesio-political respect, shows very little interest in using distinct Trinitarian terminology in his sermons. Chrysostom is, above all, concerned with the identity and the behaviour of his audience.